Ternary copolymerized pan ultrafiltration membrane substrate for carbon capture gas separation composite membrane and preparation method thereof
By designing a ternary copolymer PAN ultrafiltration membrane substrate and combining it with PP/PE composite fiber nonwoven fabric, the flexibility and interlayer bonding stability of the PAN ultrafiltration membrane are improved. This addresses the shortcomings of existing PAN ultrafiltration membrane substrates in carbon capture and gas separation composite membranes, achieving better gas transport and structural stability.
Patent Information
- Application Number
- CN202611349653.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-09-02
AI Technical Summary
Existing PAN ultrafiltration membrane substrates cannot simultaneously meet the requirements of carbon capture gas separation composite membranes for gas transport, flexibility, and interlayer bonding stability. In particular, local cracks and interlayer delamination are prone to occur during the cutting and winding process.
The ternary copolymer PAN ultrafiltration membrane substrate is adopted. The PAN functional membrane layer is formed by ternary copolymerization of acrylonitrile, methyl acrylate and sodium styrene sulfonate and combined with PP/PE composite fiber nonwoven fabric. The ester side group and sulfonic acid group are used to improve the flexibility of molecular chain. The porous membrane is prepared by non-solvent induced phase inversion method to ensure that the interlayer peel force is not less than 5.5 N/cm.
It improves the gas permeability, pore structure controllability, flexibility and interlayer bonding stability of the membrane substrate, and reduces peeling or interlayer delamination of the membrane substrate during cutting, winding and use. It is suitable for carbon capture and gas separation composite membranes.
Smart Images

Figure CN122849989B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of gas separation membrane technology, and more specifically to a ternary copolymer PAN ultrafiltration membrane substrate for carbon capture gas separation composite membranes and its preparation method. Background Technology
[0002] Gas separation membrane technology features low energy consumption, compact device structure, and relatively simple operation, and can be used for the separation and carbon capture of carbon dioxide-containing gases. Gas separation composite membranes typically consist of a porous membrane substrate and a separation layer disposed on the surface of the porous membrane substrate. The porous membrane substrate needs to provide mechanical support for the separation layer and also form gas transport channels. Especially during the coating, cutting, winding, and use of the composite membrane, the porous membrane substrate also needs to possess corresponding flexibility and interlayer bonding stability.
[0003] Polyacrylonitrile (PAN) possesses chemical resistance and film-forming properties, making it a common choice for preparing porous ultrafiltration membrane substrates. However, existing PAN ultrafiltration membranes are primarily designed for water treatment, and their functional membrane layers are typically formed using PAN homopolymers. The cyano groups in the PAN homopolymer molecular chains are arranged in a relatively regular pattern, with strong dipole interactions between chain segments. This results in membrane layers that tend to exhibit high rigidity and relatively insufficient flexibility, potentially leading to localized cracking during cutting or winding. Furthermore, the interfacial bonding strength between the nonwoven support layer and the PAN functional membrane layer in existing PAN ultrafiltration membranes is limited, making them prone to peeling or interlayer delamination during subsequent processing or use.
[0004] Furthermore, when existing PAN ultrafiltration membranes are used as gas separation composite membrane substrates, it is necessary to consider gas transport performance, membrane flexibility, and interfacial bonding stability. If the gas permeation flux is increased solely by adjusting the membrane pore structure, it may affect the structural integrity of the membrane and the coating quality of the subsequent separation layer; if the mechanical strength of the membrane or support layer is mainly increased, it may increase the stiffness of the membrane substrate and the gas transport resistance.
[0005] Therefore, existing PAN ultrafiltration membrane substrates cannot simultaneously meet the requirements of carbon capture gas separation composite membranes for gas transport, flexibility, and interlayer bonding stability. Summary of the Invention
[0006] One objective of the first aspect of the present invention is to provide a ternary copolymer PAN ultrafiltration membrane substrate for carbon capture gas separation composite membranes, thereby solving the technical problem that PAN ultrafiltration membrane substrates in the prior art cannot simultaneously meet the requirements of carbon capture gas separation composite membranes for gas transport, flexibility and interlayer bonding stability.
[0007] Another objective of the first aspect of the present invention is to balance film thickness, surface smoothness and interlayer bonding stability.
[0008] The second objective of this invention is to provide a method for preparing a ternary copolymer PAN ultrafiltration membrane substrate.
[0009] According to a first aspect of the present invention, the present invention provides a ternary copolymer PAN ultrafiltration membrane substrate for a carbon capture gas separation composite membrane, comprising a nonwoven fabric support layer and a PAN functional membrane layer disposed on one surface of the nonwoven fabric support layer, wherein the nonwoven fabric support layer is a PP / PE composite fiber nonwoven fabric; wherein, The PAN functional film layer is a ternary copolymer PAN formed by the ternary copolymerization of acrylonitrile monomer, methyl acrylate monomer and sodium styrene sulfonate monomer, wherein the molar ratio of acrylonitrile monomer, methyl acrylate monomer and sodium styrene sulfonate monomer is any value in (85-94):(4-10):(1-5); The 180° interlayer peel force between the PAN functional film layer and the PP / PE composite fiber nonwoven fabric is not less than 5.5 N / cm.
[0010] Optionally, the number-average molecular weight of the ternary copolymer PAN is any value between 30,000 g / mol and 50,000 g / mol, and the weight-average molecular weight is any value between 80,000 g / mol and 120,000 g / mol.
[0011] Optionally, the basis weight of the PP / PE composite fiber nonwoven fabric is 78.8 g / m². 2 -82.2g / m 2 The thickness is 166μm-185μm.
[0012] Optionally, the thickness of the PAN functional film layer is any value between 20μm and 50μm, and the average surface pore size of the PAN functional film layer is any value between 20nm and 30nm.
[0013] Optionally, the pore size distribution span of the PAN functional film layer is no greater than 12 nm.
[0014] According to a second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned PAN ultrafiltration membrane substrate, which employs a solvent-inducible phase inversion method and includes the following steps: The ternary copolymer PAN, solvent, and a compound pore-forming agent composed of polyethylene glycol and polyvinylpyrrolidone are mixed and stirred to obtain a casting solution. The casting solution is defoamed. The degassed casting liquid is coated onto the surface of PP / PE composite fiber nonwoven fabric, allowing some of the casting liquid to enter the interstices of the surface fibers of the PP / PE composite fiber nonwoven fabric to form a composite wet film. The composite wet membrane is immersed in an aqueous coagulation bath to perform non-solvent-induced phase separation, forming a porous primary membrane. The porous nascent membrane is sequentially washed with water and dried with a gradient temperature increase to obtain the PAN ultrafiltration membrane substrate.
[0015] Optionally, the solid content of the ternary copolymer PAN is any value between 10wt% and 20wt%.
[0016] Optionally, the porogen is a compound of polyethylene glycol and polyvinylpyrrolidone, and the content of the porogen is any value between 0.1 wt% and 10 wt%.
[0017] Optionally, the solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone.
[0018] Optionally, the temperature of the aqueous coagulation bath is any value between 10℃ and 30℃.
[0019] This invention utilizes AN / MA / SSS ternary copolymer PAN to form a functional PAN membrane. The ester side groups of the methyl acrylate monomer increase the inter-chain spacing of the polymer molecules, while the sulfonic acid groups of the sodium styrene sulfonate monomer introduce steric hindrance. Together, they weaken the strong dipole interaction between cyano groups in the PAN molecular chains, reducing the regularity and crystallinity of the molecular chain arrangement, thereby improving the flexibility of the PAN functional membrane and facilitating the regulation of the solvent-non-solvent exchange rate during the solvent-induced phase transformation process. This results in a pore structure suitable for gas transport in the obtained PAN functional membrane. Furthermore, the PP / PE composite fiber nonwoven fabric possesses corresponding air permeability and flexibility, and can form a high interlayer bonding strength with the ternary copolymer PAN functional membrane, ensuring that the 180° interlayer peel force between the two is not less than 5.5 N / cm. This reduces peeling or interlayer delamination of the membrane substrate during cutting, winding, and use, balancing the gas permeability, pore structure controllability, flexibility, and interlayer bonding stability of the membrane substrate, making it suitable for carbon capture and gas separation composite membranes.
[0020] Furthermore, the doctor blade gap of this invention is any value between 220μm and 280μm, and the film-casting speed is any value between 2m / min and 10m / min. The doctor blade gap and film-casting speed jointly affect the spreading state of the casting solution on the surface of the PP / PE composite fiber nonwoven fabric, the thickness of the composite wet film, and the degree to which some of the casting solution enters the interfiber gaps on the surface. Controlling the doctor blade gap and film-casting speed within the above ranges is beneficial for balancing film thickness, surface smoothness, and interlayer bonding stability.
[0021] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Attached Figure Description
[0022] The following sections will describe some specific embodiments of the invention in detail by way of example and not limitation, with reference to the accompanying drawings. The same reference numerals in the drawings denote the same or similar parts or portions. Those skilled in the art should understand that these drawings are not necessarily drawn to scale. In the drawings: Figure 1 This is a schematic flowchart illustrating a method for preparing a PAN ultrafiltration membrane substrate in one embodiment of this application; Figure 2 Fourier transform infrared spectrum comparison of PAN ultrafiltration membrane substrate prepared in Example 1 of this application and commercially available PAN ultrafiltration membrane in Comparative Example 4; Figure 3 This is a scanning electron microscope image of the surface of the PAN ultrafiltration membrane substrate prepared in Example 1 of this application; Figure 4 This is a cross-sectional scanning electron microscope image of the PAN ultrafiltration membrane substrate prepared in Example 1 of this application; Figure 5 This is a magnified scanning electron microscope image of a cross-section of the PAN ultrafiltration membrane substrate prepared in Example 1 of this application; Figure 6 This is a cross-sectional scanning electron microscope image of the PAN ultrafiltration membrane substrate prepared in Comparative Example 1 of this application. Detailed Implementation
[0023] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings and examples. The following examples are for illustrative purposes only and are not intended to limit the scope of the invention.
[0024] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the specific embodiments of this application will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, it should be noted that, for ease of description, only the parts relevant to this application are shown in the accompanying drawings, not the entire structure. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this application.
[0025] The terms “comprising” and “having”, and any variations thereof, used in this application are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or apparatus that includes a series of steps or units is not limited to the steps or units listed, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to such process, method, product, or apparatus.
[0026] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0027] This invention provides a ternary copolymer PAN ultrafiltration membrane substrate for carbon capture and gas separation composite membranes. The ternary copolymer PAN ultrafiltration membrane substrate includes a nonwoven support layer and a PAN functional membrane layer disposed on one side surface of the nonwoven support layer. The nonwoven support layer is a PP / PE composite fiber nonwoven fabric. The PAN functional membrane layer is a ternary copolymer PAN formed by the ternary copolymerization of acrylonitrile monomer, methyl acrylate monomer, and sodium styrene sulfonate monomer. The molar ratio of acrylonitrile monomer, methyl acrylate monomer, and sodium styrene sulfonate monomer is any value within the range of (85-94):(4-10):(1-5). The 180° interlayer peel force between the PAN functional membrane layer and the PP / PE composite fiber nonwoven fabric is not less than 5.5 N / cm. For example, the molar ratio of acrylonitrile (AN), methyl acrylate (MA), and sodium styrene sulfonate (SSS) can be 85:10:5, 86:10:4, 87:9:4, 88:8:4, 89:8:3, 90:7:3, 91:6:3, 92:6:2, 93:5:2, or 94:5:1, or any other value among (85-94):(4-10):(1-5).
[0028] In this embodiment, a PAN functional membrane layer is formed by using AN / MA / SSS ternary copolymer PAN. The ester side groups of the methyl acrylate monomer can increase the inter-chain spacing of the polymer molecules, and the sulfonic acid groups of the sodium styrene sulfonate monomer can introduce steric hindrance. Together, they weaken the strong dipole interaction between the cyano groups in the PAN molecular chain, reduce the regularity of the molecular chain arrangement and crystallinity, thereby improving the flexibility of the PAN functional membrane layer and facilitating the regulation of the solvent-non-solvent exchange rate during the non-solvent-induced phase transformation process, so that the resulting PAN functional membrane layer has a pore structure suitable for gas transport. Furthermore, the PP / PE composite fiber nonwoven fabric has corresponding air permeability and flexibility, and can form a high interlayer bonding strength with the ternary copolymer PAN functional membrane layer, so that the 180° interlayer peel force between the two is not less than 5.5 N / cm, thereby reducing peeling or interlayer delamination of the membrane substrate during cutting, winding and use, taking into account the gas permeability, pore structure controllability, flexibility and interlayer bonding stability of the membrane substrate, making it suitable for carbon capture gas separation composite membranes.
[0029] In some embodiments, the molar percentages of acrylonitrile monomer, methyl acrylate monomer, and sodium styrene sulfonate monomer are 85%-94%, 4%-10%, and 1%-5%, respectively, and the sum of their molar percentages is 100%. Within the above ranges, the acrylonitrile unit can maintain the film-forming properties, mechanical strength, solvent resistance, and heat resistance of the PAN functional film; the ester side groups in the methyl acrylate unit can increase the interchain spacing of the polymer molecules and improve chain flexibility; the sulfonic acid groups and benzene ring structure in the sodium styrene sulfonate unit can introduce polar groups and steric hindrance, further changing the regular arrangement of the PAN molecular chains and regulating the exchange process between solvent and non-solvent during phase inversion. Therefore, the above ternary composition can maintain the properties of the PAN bulk while taking into account the flexibility, film-forming stability, and tunable pore structure of the PAN functional film.
[0030] In other embodiments, when the contents of methyl acrylate units and sodium styrene sulfonate units are low, their effect on regulating the regularity and segment flexibility of the PAN molecular chain is limited; when the contents of both are high, the proportion of acrylonitrile units decreases accordingly, which may affect the mechanical strength, solvent resistance, and phase inversion film formation process of the PAN functional film. Therefore, controlling the molar percentage of the three monomers within the above-mentioned range is beneficial for achieving a balance between film strength, flexibility, and pore structure regulation.
[0031] In some embodiments, the 180° interlayer peel force between the PAN functional film layer and the PP / PE composite fiber nonwoven fabric is not less than 5.5 N / cm. This interlayer peel force indicates that the PAN functional film layer and the nonwoven fabric support layer have corresponding interfacial bonding stability, which can reduce the possibility of peeling or interlayer delamination of the membrane substrate during cutting, winding, and subsequent composite film preparation, and is beneficial to maintaining the structural integrity of the membrane substrate during use. Compared with the comparative example using PET nonwoven fabric, the PP / PE composite fiber nonwoven fabric used in this application has a higher interlayer peel force, indicating that under the casting solution composition and phase inversion conditions of this application, the PP / PE composite fiber nonwoven fabric and the ternary copolymer PAN functional film layer have a better interfacial bonding effect.
[0032] In a further embodiment, the number-average molecular weight of the ternary copolymer PAN is any value between 30,000 g / mol and 50,000 g / mol, and the weight-average molecular weight is any value between 80,000 g / mol and 120,000 g / mol. For example, in this embodiment, the number-average molecular weight of the ternary copolymer PAN can be 30,000 g / mol, 35,000 g / mol, 40,000 g / mol, 45,000 g / mol, or 50,000 g / mol, or other values within the above range. The weight-average molecular weight of the ternary copolymer PAN can be 80,000 g / mol, 90,000 g / mol, 100,000 g / mol, 110,000 g / mol, or 120,000 g / mol, or other values within the above range.
[0033] In this embodiment, when the ternary copolymer PAN is within the aforementioned number-average and weight-average molecular weight ranges, the polymer molecular chains can form a corresponding degree of entanglement, giving the casting solution a viscosity suitable for coating and phase inversion film formation, and facilitating the PAN functional film layer to obtain the corresponding mechanical strength and structural integrity. Simultaneously, the aforementioned molecular weight range allows the solvent and non-solvent to maintain a suitable exchange rate during phase inversion, thereby balancing the leveling properties of the casting solution, the film-forming stability of the PAN functional film layer, and the controllability of the pore structure.
[0034] In other embodiments, when the molecular weight of the ternary copolymer PAN is low, the degree of molecular chain entanglement is insufficient, and the mechanical strength and structural stability of the formed PAN functional film may decrease; when the molecular weight of the ternary copolymer PAN is high, the viscosity of the casting solution increases accordingly, which is not conducive to the casting solution flowing fully on the surface of the nonwoven support layer, and may slow down the exchange process between solvent and non-solvent.
[0035] In a further embodiment, the basis weight of the PP / PE composite fiber nonwoven fabric is 78.8 g / m². 2 -82.2g / m 2 The thickness is 166μm-185μm, for example, it can be 78.8g / m³. 2 79.0g / m 2 79.5g / m 2 80.0g / m 2 80.5g / m 2 81.0g / m 2 81.5g / m 2 82.0g / m 2 Or 82.2g / m 2The thickness of the PP / PE composite fiber nonwoven fabric is any value between 166μm and 185μm, for example, it can be 166μm, 170μm, 175μm, 180μm or 185μm, or other values within the above range.
[0036] In this embodiment, when the PP / PE composite fiber nonwoven fabric is within the above-mentioned basis weight and thickness range, it can provide corresponding mechanical support for the PAN functional membrane layer, reducing the deformation of the membrane substrate during the film scraping, cutting and winding process; at the same time, the nonwoven fabric can retain corresponding fiber gaps and gas transmission channels, avoiding excessive additional resistance to gas transmission by the support layer, thereby taking into account the mechanical support performance, flexibility and gas permeability performance of the membrane substrate.
[0037] In other embodiments, if the basis weight or thickness of the PP / PE composite fiber nonwoven fabric is too small, its mechanical support and dimensional stability may be insufficient; if the basis weight or thickness is too large, the overall stiffness of the nonwoven fabric and the gas transmission resistance may increase, which is not conducive to the winding process of the membrane substrate and rapid gas transmission. Therefore, the above-mentioned basis weight and thickness range is conducive to achieving a balance between mechanical support, flexibility and gas transmission performance.
[0038] In a further embodiment, the thickness of the PAN functional film layer is any value between 20μm and 50μm, for example, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, or 50μm, or other values within the above range. The average surface pore size of the PAN functional film layer is any value between 20nm and 30nm, for example, 20nm, 22nm, 24nm, 25nm, 26nm, 28nm, or 30nm, or other values within the above range. When the thickness of the PAN functional film layer is within the range of 20μm to 50μm, the continuity and structural integrity of the film layer on the surface of the nonwoven fabric support layer can be guaranteed, and it can have corresponding mechanical strength, while avoiding increased gas transmission resistance or drying shrinkage internal stress due to excessive film thickness. When the average pore size of the PAN functional membrane is in the range of 20nm-30nm, it can provide corresponding transport channels for gas, reduce the substrate's obstruction of gas transport, and reduce the excessive penetration of the subsequent separation layer coating liquid into the macroporous area, thereby taking into account the integrity of the membrane, gas transport performance, and the coating compatibility of the subsequent separation layer.
[0039] In other embodiments, if the thickness of the PAN functional film is too small, the film continuity and mechanical stability may be insufficient, making it prone to local defects; if the film thickness is too large, the gas transport path and internal stress of the film may increase. If the average surface pore size is too small, the gas transport resistance of the substrate may increase; if the average surface pore size is too large, the subsequent separation layer coating liquid may excessively penetrate into the interior of the PAN functional film, increasing the possibility of porosity or local defects.
[0040] In a further embodiment, the pore size distribution span of the PAN functional film layer is no greater than 12 nm, for example, it can be 12 nm, 11.5 nm, 11 nm, 10.5 nm, 10 nm, or 9.5 nm, or other values no greater than 12 nm. In this embodiment, the pore size distribution span is no greater than 12 nm, indicating that the pore size distribution in the PAN functional film layer is relatively concentrated, which can reduce the proportion of excessively small and large pores, so that the gas has a more uniform transport path when passing through the membrane substrate, and improve the consistency of the pore structure in different regions.
[0041] In this embodiment, by simultaneously controlling the average pore size and pore size distribution span of the PAN functional membrane layer, not only can the pore size of the membrane layer be concentrated in a range suitable for gas transport, but also the large pore ends in the pore size distribution can be limited. This reduces the gas transport resistance of the substrate while providing a support surface with a more uniform pore structure for the subsequent dense separation layer, which is beneficial to improving the film formation integrity and performance stability of the composite gas separation membrane.
[0042] Figure 1 This is a schematic flowchart illustrating a method for preparing a PAN ultrafiltration membrane substrate in one embodiment of this application.
[0043] like Figure 1 As shown, the present invention also provides a method for preparing the above-mentioned PAN ultrafiltration membrane substrate, which employs a solvent-inducible phase inversion method and includes the following steps: Step S100: Mix the ternary copolymer PAN, solvent and compound pore-forming agent composed of polyethylene glycol and polyvinylpyrrolidone, and stir to obtain casting solution; Step S200: Degas the casting solution; Step S300: The degassed casting solution is coated onto the surface of the PP / PE composite fiber nonwoven fabric, so that some of the casting solution enters the interstices of the surface fibers of the PP / PE composite fiber nonwoven fabric to form a composite wet film. Step S400: Immerse the composite wet membrane in an aqueous coagulation bath for non-solvent-induced phase separation to form a porous primary membrane; Step S500: The porous nascent membrane is sequentially washed with water and dried with gradient temperature to obtain the PAN ultrafiltration membrane substrate.
[0044] The method for preparing the PAN ultrafiltration membrane substrate provided in this embodiment includes the following steps: Ternary copolymer PAN, solvent, and a compound pore-forming agent composed of polyethylene glycol and polyvinylpyrrolidone are added to a stirring container for mixing and stirring to fully dissolve the ternary copolymer PAN and obtain a uniform casting solution; subsequently, the casting solution is degassed to remove air bubbles; the degassed casting solution is coated onto one side of a PP / PE composite fiber nonwoven fabric, and the casting solution spreads on the surface of the nonwoven fabric, allowing part of the casting solution to be cast. The membrane solution enters the interstices of the surface fibers of the nonwoven fabric, forming a composite wet membrane composed of a casting solution layer and a PP / PE composite fiber nonwoven fabric. The composite wet membrane is then immersed in a coagulation bath with water as the non-solvent, causing the solvent in the casting solution to diffuse into the coagulation bath, while the water in the coagulation bath diffuses into the interior of the casting solution. This results in non-solvent-induced phase separation and solidification to form a porous nascent membrane. The porous nascent membrane is then washed with water to remove residual solvent and pore-forming agent, followed by gradient temperature drying and winding to obtain the PAN ultrafiltration membrane substrate.
[0045] This embodiment employs a solvent-inducing phase inversion method to prepare the PAN ultrafiltration membrane substrate. A casting solution containing ternary copolymer PAN and a compound pore-forming agent is coated onto the surface of a PP / PE composite fiber nonwoven fabric, allowing some of the casting solution to penetrate the interfiber spaces on the surface of the nonwoven fabric. After the composite wet membrane enters an aqueous coagulation bath, the solvent in the casting solution diffuses bidirectionally with the water in the coagulation bath, causing phase separation of the ternary copolymer PAN and solidification to form a porous PAN functional membrane layer. Simultaneously, the PAN functional membrane layer forms an interfacial bond with the PP / PE composite fiber nonwoven fabric. Subsequent water washing removes residual solvent and pore-forming agent from the membrane, while gradient temperature drying reduces membrane shrinkage and internal stress caused by rapid water loss. This method balances the controllability of the pore structure of the PAN functional membrane layer, membrane surface integrity, and the bonding stability with the nonwoven fabric support layer. Furthermore, this method can be used in phase inversion membrane fabrication production lines, making it suitable for continuous production.
[0046] In a further embodiment, the solid content of the ternary copolymer PAN is any value between 10wt% and 20wt%, for example, it can be 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, or 20wt%, or other values within the above range. When the solid content of the ternary copolymer PAN is within the above range, it enables the casting solution to have a viscosity suitable for coating and leveling on the surface of PP / PE composite fiber nonwoven fabric, and enables the PAN molecular chains to have a corresponding degree of entanglement, thereby facilitating the formation of a continuous PAN functional film layer.
[0047] In other embodiments, when the solid content is low, the viscosity of the casting solution and the degree of PAN molecular chain entanglement may be insufficient, making it easy to form large-sized pore structures or local film-forming defects during the phase transformation process. When the solid content is high, the viscosity of the casting solution increases accordingly, and the leveling properties of the casting solution and the exchange rate between solvent and non-solvent may decrease, thereby increasing the gas transport resistance.
[0048] In a further embodiment, the pore-forming agent is a compound of polyethylene glycol and polyvinylpyrrolidone, and the content of the pore-forming agent is any value from 0.1wt% to 10wt%, for example, it can be 0.1wt%, 2wt%, 4wt%, 6wt%, 8wt%, or 10wt%, or other values within the above range. Both polyethylene glycol and polyvinylpyrrolidone can participate in regulating the viscosity of the casting solution and the mass transfer behavior during the phase transformation process, and dissolve from the primary film during water washing, thereby forming the corresponding porous structure in the PAN functional film layer.
[0049] In a further embodiment, the solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone. These solvents are all polar aprotic solvents capable of dissolving ternary copolymer PAN, which is beneficial for forming a casting solution with a relatively uniform component distribution between the ternary copolymer PAN and the compounded pore-forming agent. After the composite wet membrane enters the aqueous coagulation bath, the solvents can exchange with water and gradually diffuse out of the casting solution, thereby inducing phase separation of the ternary copolymer PAN and the formation of a porous membrane structure. When two or more solvents are used, the phase separation process can be adjusted by the solubility of different solvents and their exchange behavior with water.
[0050] In a further embodiment, the temperature of the aqueous coagulation bath is any value between 10°C and 30°C, for example, 10°C, 15°C, 20°C, 25°C, or 30°C, or other values within the above range. The temperature of the aqueous coagulation bath can affect the exchange rate between the solvent and water, as well as the phase separation rate of the ternary copolymer PAN. When the coagulation bath temperature is too low, the exchange rate between the solvent and water is relatively slow, the formed PAN functional film tends to be dense, and the gas transport resistance may increase; when the coagulation bath temperature is too high, the exchange rate between the solvent and water is accelerated, which may form a larger pore structure or a non-uniform pore structure. Controlling the temperature of the aqueous coagulation bath within the above range is beneficial for stabilizing the phase separation process and obtaining a PAN functional film that balances gas transport performance, pore size distribution, and film integrity.
[0051] In some embodiments, the ternary copolymer PAN, solvent, and compounded porogen are mixed and then heated and stirred until the ternary copolymer PAN is fully dissolved to form a uniform casting solution. Heating and stirring can improve the dissolution efficiency of the ternary copolymer PAN and facilitate the uniform dispersion of the compounded porogen in the casting solution. Subsequently, the casting solution is transferred to a sealed degassing container for vacuum settling and degassing to remove air bubbles introduced during stirring, reducing the possibility of pinholes or localized pore defects formed by air bubbles during subsequent coating and phase transformation processes.
[0052] In step S300, a coating blade can be used to coat the degassed casting solution onto the surface of the PP / PE composite fiber nonwoven fabric. The coating thickness of the composite wet film and the spreading state of the casting solution on the PP / PE composite fiber nonwoven fabric surface are controlled by adjusting the gap between the coating blade and the PP / PE composite fiber nonwoven fabric, as well as the moving speed of the PP / PE composite fiber nonwoven fabric relative to the coating blade. During the coating process, some of the casting solution enters the interfiber gaps on the surface of the PP / PE composite fiber nonwoven fabric to form a composite wet film composed of the casting solution layer and the PP / PE composite fiber nonwoven fabric.
[0053] In this embodiment, the doctor blade gap is any value between 220μm and 280μm, for example, it can be 220μm, 230μm, 240μm, 250μm, 260μm, 270μm, or 280μm, or other values within the above range. The casting speed is any value between 2m / min and 10m / min, for example, it can be 2m / min, 4m / min, 6m / min, 8m / min, or 10m / min, or other values within the above range. The doctor blade gap and the casting speed together affect the spreading state of the casting solution on the surface of the PP / PE composite fiber nonwoven fabric, the thickness of the composite wet film, and the degree to which some of the casting solution enters the interfiber gaps on the surface. When the doctor blade gap is too small, the interference between the doctor blade and the raised fibers on the nonwoven fabric surface increases, which may reduce the leveling properties of the casting solution and make the film surface prone to defects such as orange peel texture. When the doctor blade gap is too large, the formed PAN functional film layer is thicker, the shrinkage internal stress during the drying process increases, and peeling or delamination may occur during cutting. Controlling the doctor blade gap and the film-casting speed within the above range is beneficial to balancing film thickness, surface smoothness, and interlayer bonding stability.
[0054] In some embodiments, the porous nascent membrane sequentially passes through multiple rinsing tanks at temperatures of 45°C, 50°C, 55°C, and 60°C in the transport direction to gradually remove residual solvents and pore-forming agents from the membrane. After rinsing, the porous nascent membrane is then sequentially passed through multiple drying zones at temperatures of 35°C, 45°C, and 55°C for gradient temperature drying. Gradually increasing the rinsing temperature improves the diffusion and elution efficiency of residual solvents and pore-forming agents into the water, and reduces the impact of sudden temperature changes on the membrane structure when directly entering a higher-temperature rinsing tank. Gradually increasing the temperature during drying allows for the gradual removal of moisture from the membrane, reducing local shrinkage and internal stress caused by rapid water loss, thereby reducing the possibility of membrane curling, pore structure deformation, and delamination between the PAN functional membrane layer and the nonwoven support layer.
[0055] The technical solution of this application will be further described below with reference to specific embodiments.
[0056] Example 1 The preparation method of PAN ultrafiltration membrane substrate includes the following steps: Weigh out 14wt% of AN / MA / SSS ternary copolymer PAN powder (purchased from Qilu Branch of China Petroleum & Chemical Corporation, brand: modified acrylonitrile polymer A-7), 6wt% of compound porogen, and add 80wt% of solvent N,N-dimethylformamide (DMF). The compound porogen is formed by compounding polyethylene glycol (purchased from Beijing Innocare Technology Co., Ltd., brand: A04817, CAS No.: 25322-68-3) with an average molecular weight of approximately 400 g / mol and polyvinylpyrrolidone (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., brand: P110607, CAS No.: 9003-39-8) with a K value grade of K30. The molar ratio of acrylonitrile monomer, methyl acrylate monomer and sodium styrene sulfonate monomer in the ternary copolymer PAN is any value of 90:7:3. The above components were added to a closed reaction vessel equipped with mechanical stirring and stirred continuously in a 60°C water bath for 6 hours until PAN was completely dissolved, forming a uniform and transparent casting solution. The casting solution was then transferred to a vacuum degassing kettle and vacuum degassed at room temperature for 2 hours. The blade gap was set to 260 μm, and the casting solution was uniformly coated onto the surface of the PP / PE composite nonwoven fabric support layer at a speed of 8 m / min. The membrane was then immersed in a 20°C deionized water coagulation bath to complete the phase transformation, resulting in a white, opaque primary membrane. The nascent membrane is sequentially rinsed in rinsing tanks at different temperatures to remove residual DMF solvent and pore-forming agents. The PAN ultrafiltration membrane substrate is dried in a gradient temperature oven to obtain the final product.
[0057] Example 2 The only difference between Example 2 and Example 1 is that the PAN solid content is 12wt%, the DMF solvent is 82wt%, and the pore-forming agent is 6wt%.
[0058] Example 3 The only difference between Example 3 and Example 1 is that the PAN solid content is 16wt%, the DMF solvent is 78wt%, and the pore-forming agent is 6wt%.
[0059] Example 4 The only difference between Example 4 and Example 1 is the scraper gap of 240μm.
[0060] Example 5 The only difference between Example 5 and Example 1 is the scraper gap of 280μm.
[0061] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that the ternary copolymer PAN was replaced with pure PAN homopolymer (purchased from Shanghai Maclean Biochemical Technology Co., Ltd., brand name: P823208, CAS number: 25014-41-9), with CAS number 25014-41-9.
[0062] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that the PP / PE composite nonwoven fabric is replaced with PET nonwoven fabric.
[0063] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that the ternary copolymer PAN was replaced with pure PAN homopolymer, and the PP / PE composite nonwoven fabric was replaced with PET nonwoven fabric.
[0064] Comparative Example 4 The only difference between Comparative Example 4 and Example 1 is that the ultrafiltration membrane is a commercially available PAN ultrafiltration membrane, which was purchased from Guochu Technology (Xiamen) Co., Ltd., product model TFK-100K series.
[0065] Figure 2 This is a comparison of the Fourier transform infrared spectra of the PAN ultrafiltration membrane substrate prepared in Example 1 of this application and the commercially available PAN ultrafiltration membrane in Comparative Example 4. Figure 3 This is a scanning electron microscope image of the surface of the PAN ultrafiltration membrane substrate prepared in Example 1 of this application. Figure 4 This is a cross-sectional scanning electron microscope image of the PAN ultrafiltration membrane substrate prepared in Example 1 of this application. Figure 5 This is a magnified scanning electron microscope image of a cross-section of the PAN ultrafiltration membrane substrate prepared in Example 1 of this application. Figure 6 This is a cross-sectional scanning electron microscope image of the PAN ultrafiltration membrane substrate prepared in Comparative Example 1 of this application. Figure 4 and Figure 6To characterize the cross-sectional morphology of the PAN ultrafiltration membrane substrate using a SU8600 scanning electron microscope, the accelerating voltage was 5.00 kV, the working distance was 9.5 mm, the magnification was 1000x, and the imaging mode was UD (+LD). The scale bar in the image is 50.0 μm. Figure 5 The local cross-sectional morphology of the PAN ultrafiltration membrane substrate was characterized using a SU8600 scanning electron microscope. The accelerating voltage was 5.00 kV, the working distance was 8.9 mm, the magnification was 20,000, and the imaging mode was UD (+LD). The scale bar in the figure is 2.00 μm.
[0066] To characterize the chemical composition and microstructure of the PAN ultrafiltration membrane substrate obtained in Example 1, Fourier transform infrared spectroscopy was performed on Example 1 and Comparative Example 4, and surface and cross-sectional scanning electron microscopy was performed on Example 1, yielding the following results: Figures 2 to 5 The test results are shown.
[0067] like Figure 2 As shown, both Example 1 and Comparative Example 4 are at 2243 cm. -1 The presence of characteristic absorption peaks for nitrile groups nearby indicates that both contain PAN basic segments formed from acrylonitrile units. Compared to Comparative Example 4, Example 1 showed a peak at 1731 cm⁻¹. -1 A relatively clear characteristic absorption peak of ester carbonyl group appeared nearby. This characteristic absorption peak corresponds to the methyl acrylate unit in the ternary copolymer PAN, indicating that the film-forming polymer used in Example 1 introduced methyl acrylate copolymer units into the basic PAN chain segment, and was not composed only of acrylonitrile units.
[0068] like Figure 3 As shown, the PAN functional film obtained in Example 1 has a large number of nanoscale pore structures distributed on its surface. The pore sizes indicated in the figure are mainly in the range of 19.1 nm to 28.3 nm, and the pore size distribution is relatively uniform. No large through pores with prominent sizes were observed. This surface morphology is consistent with the test results in Table 1, which show that the average pore size of Example 1 is 24.3 nm and the pore size distribution span is 11.5 nm. This indicates that the ternary copolymer PAN composition and phase transformation conditions used can form a surface pore structure suitable for gas transport and can be coated with a dense separation layer.
[0069] like Figure 4 As shown, the cross-sectional thickness of the PAN functional membrane obtained in Example 1 is approximately 35.2 μm, falling within the set range of 20 μm-50 μm. The PAN functional membrane has a surface porous structure and porous sublayers extending along the thickness direction, with corresponding through-channels formed in the sublayers, which helps to shorten the gas transport path inside the membrane substrate. No obvious interface gaps or delamination were observed between the PAN functional membrane and the underlying nonwoven support layer, indicating that the two maintain continuous bonding within the observed cross-section.
[0070] like Figure 5 As shown, at higher magnifications, the surface structure of the PAN functional membrane layer obtained in Example 1 is continuous, with a porous sublayer composed of relatively uniform micropores formed beneath it. The transition between the surface layer and the porous sublayer is continuous, and no obvious cracks or through-hole defects were observed. This porous sublayer can provide corresponding channels for gas transport, and the continuous surface structure is beneficial for providing a more uniform coating surface for the subsequent dense separation layer, reducing the possibility of excessive penetration of the coating liquid into local macropores and the formation of pore leakage defects. The performance and structure of the PAN ultrafiltration membrane substrates in Examples 1-5 and Comparative Examples 1-3 were tested, and the test results are shown in Table 1.
[0071] Table 1. Performance and structural test results of PAN ultrafiltration membrane substrates in Examples 1-5 and Comparative Examples 1-3
[0072] The test methods for each parameter in Table 1 are as follows: (1) CO2 permeation flux: Measured using a constant pressure variable volume method single-component gas permeation analyzer. The PAN ultrafiltration membrane substrate was cut into sections with an effective test area of 7.065 cm². 2 A circular sample was tested at a pressure of 0.05 MPa and a temperature of 25°C. o C. The test gas is high-purity CO2 (purity ≥ 99.99%), and the gas permeation rate is measured using a soap bubble flow meter. The gas permeation rate can be calculated using the following formula: ; in the formula It is gas permeability (1 GPU = 10 -6 cm 3 (STP) cm -2 s -1 cmHg), The transmembrane pressure difference (atm) is the pressure difference between the membrane and the membrane. Represents the effective membrane area (m²) 2 ), It is a test temperature ( o C), Atmospheric pressure (atm). dV / dT This represents the rate of change of volume in the soap bubble flow meter over time.
[0073] (2) Average pore size and pore size distribution span: The average pore size and pore size distribution span were determined by scanning electron microscopy and ImageJ image analysis software (Reference: J. Membr. Sci. 2001, 186(1): 85-96; J. Membr. Sci. 2006, 283(1):109-115). PAN ultrafiltration membrane substrates were cut into samples of approximately 5mm × 5mm, sputter-coated with gold, and placed on a scanning electron microscope stage. Surface morphology images of the PAN functional membrane layer were acquired under accelerating voltage of 5.00kV and magnification of 50,000x. The obtained SEM images were imported into ImageJ image analysis software. By setting a grayscale threshold, the images were binarized to separate the pore structure region from the polymer substrate region. The pore structures in the binarized images were identified and statistically analyzed. Each pore was considered equivalent to a circle, and ImageJ software automatically calculated the equivalent pore diameter of each pore. The equivalent pore diameter data of all pores were statistically analyzed to obtain the pore diameter distribution. The surface average pore diameter was taken as the arithmetic mean of the equivalent pore diameters of all statistically analyzed pores. The pore diameter distribution span was represented by the difference between the largest and smallest equivalent pore diameters in the pore diameter distribution. At least five different fields of view were selected for each sample for statistical analysis, and the results were expressed as an arithmetic mean.
[0074] (3) Dry tensile strength and dry elongation at break: determined using a universal testing machine (GB / T 1040). Dumbbell-shaped specimens with a width of 10 mm and a gauge length of 50 mm were cut longitudinally along the PAN ultrafiltration membrane substrate. At least five parallel specimens were prepared per group. The tensile rate was 5 mm / min, and the initial clamping distance was 50 mm. The specimens were clamped in the upper and lower clamps and stretched at a rate of 5 mm / min until fracture. The force-displacement curve was recorded. The dry tensile strength σ was calculated using the formula σ = F. max Calculate / (b×d), where F max The maximum tensile force is given by b, the specimen width is given by d, and the total specimen thickness is given by d. The dry elongation at break ε is calculated using the formula ε=(ΔL / L0)×100%, where ΔL is the gauge length elongation at break and L0 is the initial gauge length. The results are expressed as the arithmetic mean of 5 parallel specimens.
[0075] (4) 180° interlayer peel force: The 180° peel test was used to determine the peel force (GB / T 2792-2023). The PAN ultrafiltration membrane substrate was cut into strips with a width of 25 mm and a length of 150 mm. The PAN functional membrane layer and the nonwoven support layer were pre-peeled about 30 mm apart from one end, with no less than 5 parallel strips per group. The stretching rate was 10 mm / min and the peeling angle was 180°. The pre-peeled PAN functional membrane layer was clamped in the upper clamp and the nonwoven support layer was clamped in the lower clamp. The peeling was performed at a rate of 10 mm / min, and the peeling length was no less than 50 mm. The 180° interlayer peel force F was taken as the average peel force in the peeling stage (excluding the initial 10 mm and the last 10 mm) of the peeling force-displacement curve, and calculated according to the formula F=Favg / b was calculated, and the result is expressed in N / cm. The result is expressed as the arithmetic mean of 5 parallel samples.
[0076] (5) Evaluation of peeling during cutting: The PAN ultrafiltration membrane substrate is laid flat on a hard table. A square cutter with a specification of 100mm×100mm (blade angle of 20°, high-speed steel material) is used to cut the membrane sample in one go with uniform pressure. After cutting, the cut edge and membrane surface are observed with the naked eye under natural light (with a 10x magnifying glass if necessary). The focus is on whether peeling or delamination occurs between the PAN functional membrane layer and the non-woven support layer. If there is no peeling or delamination on the cut edge and membrane surface, it is recorded as "no peeling". Otherwise, it is recorded as "peeling". Each group of cuts shall have no less than 3 parallel samples. If all samples are free of peeling, it is judged as "no peeling". Otherwise, it is judged as "peeling".
[0077] (6) Evaluation of membrane surface defects: Observe the membrane surface defects using an optical microscope (such as Olympus BX53 or equivalent precision) at 100x magnification. Cut approximately 10mm × 10mm samples from different locations on the PAN ultrafiltration membrane substrate (membrane center, 1 / 2 radius, near the edge), and place them on the stage with the PAN functional membrane surface facing upwards. First, focus on observing the overall morphology at 50x magnification, and then switch to 100x magnification to observe the details, focusing on pinholes (circular or elliptical through holes with a diameter greater than 5μm) and orange peel texture (irregular uneven texture on the membrane surface). Observe each sample in no less than 5 fields of view, and take the most severe defect in all fields of view as the final result, and record them as "no pinholes, no orange peel texture", "pinholes, no orange peel texture", "no pinholes, orange peel texture", or "pinholes, orange peel texture".
[0078] As shown in Table 1, in Example 2, after reducing the PAN solids content from 14 wt% in Example 1 to 12 wt%, the CO2 permeation flux decreased from 11.6 × 10⁻⁶. 4 GPU performance increased to 15.2×10 4 The GPU exhibits an increased pore size distribution span of 15.4 nm and surface pinholes. This indicates that a lower PAN solid content is beneficial for improving gas permeation flux, but a decrease in casting solution viscosity and molecular chain entanglement makes it easier to form larger through-pores and widen the pore size distribution.
[0079] In Example 3, after increasing the PAN solid content to 16 wt%, the average surface pore size decreased to 21.1 nm, the pore size distribution span decreased to 9.8 nm, and the dry tensile strength increased to 47.5 MPa. No pinholes or orange peel texture appeared on the membrane surface, but the CO2 permeation flux decreased to 8.7 × 10⁻⁶. 4GPU. This indicates that increasing the PAN solids content is beneficial for forming a membrane with smaller pore size, narrower distribution, and higher mechanical strength, but it will correspondingly increase gas transport resistance. In Example 1, with a PAN solids content of 14 wt%, the CO2 permeation flux reached 11.6 × 10⁻⁶. 4 The GPU has an average surface pore size of 24.3 nm and a pore size distribution span of 11.5 nm. The membrane surface is free of pinholes and orange peel texture, achieving a good balance between gas permeation flux, pore size distribution and membrane integrity.
[0080] When the doctor blade gap was reduced from 260 μm to 240 μm, orange peel texture appeared on the film surface in Example 4, indicating that when the doctor blade gap was too small, interference between the doctor blade and the protruding fibers on the nonwoven fabric surface, as well as insufficient leveling of the casting solution, may affect the smoothness of the film surface. When the doctor blade gap was increased to 280 μm, although no pinholes or orange peel texture appeared in Example 5, peeling occurred during cutting, indicating that when the film layer is thicker, the internal stress generated by drying shrinkage may increase. When Example 1 used a doctor blade gap of 260 μm, the film surface was defect-free and there was no peeling after cutting, indicating that this doctor blade gap can take into account the leveling of the casting solution, the film structure, and the stability of interlayer bonding.
[0081] Both Example 1 and Comparative Example 1 used PP / PE composite fiber nonwoven fabric as the support layer. The only difference between them was that the film-forming polymers were ternary copolymer PAN and PAN homopolymer, respectively. Compared with Comparative Example 1, the CO2 permeation flux of Example 1 increased from 6.2 × 10⁻⁶. 4 GPU performance increased to 11.6×10 4 The pore size distribution span of the GPU decreased from 19.7 nm to 11.5 nm, the dry-state elongation at break increased from 12.6% to 31.2%, and the membrane surface changed from having pinholes to being pinhole-free. These results indicate that the introduction of MA and SSS copolymer units is beneficial for improving the flexibility and pore structure uniformity of the PAN membrane and reducing the gas transport resistance of the membrane substrate. The dry-state tensile strength of Comparative Example 1 was 51.3 MPa, higher than the 42.6 MPa of Example 1, indicating that ternary copolymer modification mainly improves flexibility and pore structure, and does not simultaneously improve all mechanical properties.
[0082] Both Example 1 and Comparative Example 2 used ternary copolymer PAN, the only difference being the support layer, which was PP / PE composite fiber nonwoven fabric and PET nonwoven fabric, respectively. The average surface pore size, pore size distribution span, tensile strength, and elongation at break were similar in both examples. However, the 180° interlaminar peel force of Example 1 was 5.7 N / cm, nearly twice that of Comparative Example 2, and Example 1 showed no peeling after cutting, while Comparative Example 2 exhibited peeling. Meanwhile, the CO2 permeation flux of Example 1 was 11.6 × 10⁻⁶. 4 The GPU is higher than the 9.3×10 in Comparison 2. 4GPU. This indicates that the PP / PE composite fiber nonwoven fabric mainly improves the interlayer bonding stability of the membrane substrate and helps reduce the gas transport resistance formed by the support layer.
[0083] Comparative Example 3, which uses both PAN homopolymer and PET nonwoven fabric, has a CO2 permeation flux, dry breaking elongation, and 180° interlayer peel force of 4.7 × 10⁻⁶. 4 GPU, 10.3%, and 2.6 N / cm, with pinholes and peeling after cutting. The corresponding values for Example 1 are 11.6 × 10⁻⁶. 4 GPU, 31.2%, and 5.7 N / cm indicate that the ternary copolymer PAN and PP / PE composite fiber nonwoven fabric play a role in the membrane pore structure and flexibility, the interfacial bonding of the support layer, and gas transport, respectively, so that the resulting membrane substrate can take into account gas permeability, mechanical flexibility, pore structure uniformity, and interlayer bonding stability.
[0084] like Figure 6 As shown, although the PAN functional film layer formed by PAN homopolymer in Comparative Example 1 has a large number of nanoscale pore structures, the pore size varies greatly in different regions, with small pores coexisting with locally larger pores, and some pores having irregular shapes. The uniformity of the surface pore structure is lower than that of Example 1. This morphology is consistent with the test results in Table 1, where the average surface pore size of Comparative Example 1 is 31.5 nm, the pore size distribution span is 19.7 nm, and pinholes are present. In contrast, the average surface pore size and pore size distribution span of Example 1 are 24.3 nm and 11.5 nm, respectively, and... Figure 4 and Figure 5 The porous structure shown is relatively continuous and uniform. This indicates that the pore structure formed by the PAN homopolymer during phase transformation is relatively incompatible, with localized large pores coexisting with denser regions, resulting in poor continuity of the effective gas transport channels. Its CO2 permeability is only 6.2 × 10⁻⁶. 4 GPU, lower than 11.6 × 10 in Example 1 4 GPU; meanwhile, localized macropores and pinholes may also affect the uniform coating of the subsequent PDMS separation layer, which corresponds to the lower CO2 permeability and ideal CO2 / N2 separation selectivity of the composite membrane in Comparative Example 1 in Table 2.
[0085] PDMS dense separation layers were coated onto the PAN ultrafiltration membrane substrates prepared in Examples 1-5 and Comparative Examples 1-3, respectively. The CO2 permeation flux and ideal CO2 / N2 separation selectivity of each composite membrane were simultaneously tested using a constant pressure variable volume method single-component gas permeation tester to evaluate the final separation performance of the carbon capture composite membranes on different substrates. The test results are shown in Table 2. Specifically, the coating method of the PDMS dense separation layer is as follows: PDMS prepolymer was dissolved in n-heptane to form a homogeneous solution, and then tetraethyl orthosilicate (TEOS) crosslinking agent and dibutyltin dilaurate (DBTDL) catalyst were added. The mass ratio of PDMS prepolymer to TEOS and DBTDL was 5:4:4. After reacting at 35°C for 2 hours, the mixed solution forms a partially cross-linked PDMS solution. Each batch of PAN ultrafiltration membrane substrate is cut into A4-sized standard samples and the surface moisture is wiped dry with lint-free paper. The partially cross-linked PDMS solution is uniformly coated onto the surface of each batch of PAN ultrafiltration membrane using a wire rod. The membrane is then cured at 80°C for 2 hours to completely cross-link and cure the PDMS, thus obtaining a PDMS / PAN composite gas separation membrane.
[0086] Table 2. Test results of composite gas separation membranes for CO2 in Examples 1-5 and Comparative Examples 1-3
[0087] The test methods for each parameter in Table 2 refer to GB / T40260-2021 Test Method for Gas Permeability Performance of Polymer Membrane Materials: Each group of PDMS / PAN composite gas separation membranes is installed in a constant pressure variable volume method single-component gas permeation tester, and tested at 25℃ using single-component CO2 and N2 respectively. The CO2 permeation flux and N2 permeation flux of each composite gas separation membrane are measured, and the ideal separation selectivity of CO2 / N2 is calculated based on the ratio of CO2 permeation flux to N2 permeation flux.
[0088] As shown in Table 2, after forming a dense PDMS separation layer on the surface of each PAN ultrafiltration membrane substrate using the same process, the pore structure and surface state of different substrates still affect the CO2 permeation flux and the ideal CO2 / N2 separation selectivity of the composite gas separation membrane.
[0089] The composite membrane in Example 2 exhibits the highest CO2 permeation flux, at 9.7 × 10⁻⁶. 3 The GPU was used, but the ideal CO2 / N2 separation selectivity was only 7.3. Considering that the pore size distribution span of Example 2 in Table 1 is 15.4 nm and surface pinholes are present, it can be seen that larger pore sizes are beneficial for increasing gas permeation flux, but may lead to excessive penetration of the PDMS coating liquid into the large-pore area or the formation of localized uneven coating, thereby reducing selectivity.
[0090] Example 3 has a smaller average pore size and pore size distribution range, and its composite membrane achieves an ideal CO2 / N2 separation selectivity of 10.1, but the CO2 permeation flux decreases to 5.6 × 10⁻⁶. 3 The GPU indicates that a denser substrate pore structure is beneficial for maintaining the integrity of the separation layer, but it increases gas transport resistance. The CO2 permeation flux and ideal CO2 / N2 separation selectivity of Example 1 are 7.4 × 10⁻⁶. 3 GPU and 9.8 achieved a relatively balanced result between penetration flux and selectivity.
[0091] The ideal CO2 / N2 separation selectivity of the composite membrane obtained in Example 4 was 8.9, lower than that in Example 1. Combined with the presence of orange peel texture on its substrate, this indicates that the surface smoothness of the substrate affects the coating uniformity of the dense PDMS separation layer. The composite membrane in Example 5 has a CO2 / N2 ideal separation selectivity of 7.6 × 10⁻⁶. 3 The GPU exhibits a CO2 permeation flux and an ideal CO2 / N2 separation selectivity of 9.6, but its substrate shows peeling after cutting, indicating that the gas separation performance test results cannot fully reflect the structural stability of the membrane substrate during processing such as cutting and winding.
[0092] Compared to Comparative Example 1, the CO2 permeation flux of the composite membrane in Example 1 increased from 4.2 × 10⁻⁶ to 4.2 × 10⁻⁶. 3 GPU performance increased to 7.4×10 3 The ideal CO2 / N2 separation selectivity of the GPU improved from 6.8 to 9.8, indicating that the more uniform pore structure and pinhole-free surface formed by the ternary copolymer PAN are beneficial for balancing the gas permeation flux and selectivity of the PDMS composite membrane. Compared with Comparative Example 2, the CO2 permeation flux and selectivity of Example 1 increased from 6.9 × 10⁻⁶ to 9.8. 3 GPU performance has been improved from 9.4 to 7.4×10. 3 The separation performance of GPU and 9.8 is relatively similar, but Example 1 exhibits higher interlayer peel strength and better cutting stability, indicating that the main function of the PP / PE support layer is to reduce substrate transport resistance and improve processing stability. The CO2 permeation flux and selectivity of the composite membrane obtained in Comparative Example 3 are only 3.7 × 10⁻⁶. 3 GPU and 5.9 are the lowest in each group, further illustrating that the non-uniform pore structure formed by PAN homopolymer and the weak interfacial bonding of PET nonwoven fabric are not conducive to the composite gas separation membrane achieving performance that balances flux and selectivity.
[0093] In summary, ternary copolymer PAN primarily improves the flexibility, pore size distribution, and gas transport performance of the PAN functional membrane layer, while PP / PE composite fiber nonwoven fabric mainly enhances interlayer bonding stability and reduces gas transport resistance in the support layer. Further adjustments to the PAN solids content and doctor blade gap allow for control of the membrane pore structure, surface condition, and processing stability. Example 1 achieved a relatively balanced result among CO2 permeation flux, pore size distribution, elongation at break, interlayer peel force, and flux and selectivity after PDMS coating, making it suitable as a porous support substrate for carbon capture and gas separation composite membranes.
[0094] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0095] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A ternary copolymer PAN ultrafiltration membrane substrate for carbon capture and gas separation composite membranes, characterized in that, It includes a nonwoven fabric support layer and a PAN functional film layer disposed on one surface of the nonwoven fabric support layer, wherein the nonwoven fabric support layer is a PP / PE composite fiber nonwoven fabric; wherein, The PAN functional film layer is a ternary copolymer PAN formed by the ternary copolymerization of acrylonitrile monomer, methyl acrylate monomer and sodium styrene sulfonate monomer, wherein the molar ratio of acrylonitrile monomer, methyl acrylate monomer and sodium styrene sulfonate monomer is any value in (85-94):(4-10):(1-5); The 180° interlayer peel force between the PAN functional film layer and the PP / PE composite fiber nonwoven fabric is not less than 5.5 N / cm.
2. The ternary copolymer PAN ultrafiltration membrane substrate according to claim 1, characterized in that, The ternary copolymer PAN has a number-average molecular weight of any value between 30,000 g / mol and 50,000 g / mol, and a weight-average molecular weight of any value between 80,000 g / mol and 120,000 g / mol.
3. The ternary copolymer PAN ultrafiltration membrane substrate according to claim 1, characterized in that, The basis weight of the PP / PE composite fiber nonwoven fabric is 78.8 g / m². 2 -82.2g / m 2 The thickness is 166μm-185μm.
4. The ternary copolymer PAN ultrafiltration membrane substrate according to claim 1, characterized in that, The thickness of the PAN functional film layer is any value between 20μm and 50μm, and the average surface pore size of the PAN functional film layer is any value between 20nm and 30nm.
5. The ternary copolymer PAN ultrafiltration membrane substrate according to claim 4, characterized in that, The pore size distribution span of the PAN functional film is no greater than 12 nm.
6. A method for preparing a PAN ultrafiltration membrane substrate according to any one of claims 1-5, characterized in that, The solvent-inducible phase transformation method includes the following steps: The ternary copolymer PAN, solvent, and a compound pore-forming agent composed of polyethylene glycol and polyvinylpyrrolidone were mixed and stirred to obtain a casting solution. The casting solution is defoamed. The degassed casting liquid is coated onto the surface of PP / PE composite fiber nonwoven fabric, allowing some of the casting liquid to enter the interstices of the surface fibers of the PP / PE composite fiber nonwoven fabric to form a composite wet film. The composite wet membrane is immersed in an aqueous coagulation bath to perform non-solvent-induced phase separation, forming a porous primary membrane. The porous nascent membrane is sequentially washed with water and dried with a gradient temperature increase to obtain the PAN ultrafiltration membrane substrate.
7. The method for preparing the ternary copolymer PAN ultrafiltration membrane substrate according to claim 6, characterized in that, The solid content of the ternary copolymer PAN is any value between 10wt% and 20wt%.
8. The method for preparing the ternary copolymer PAN ultrafiltration membrane substrate according to claim 6, characterized in that, The porogen is a compound of polyethylene glycol and polyvinylpyrrolidone, and the content of the porogen is any value between 0.1wt% and 10wt%.
9. The method for preparing the ternary copolymer PAN ultrafiltration membrane substrate according to claim 6, characterized in that, The solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone.
10. The method for preparing the ternary copolymer PAN ultrafiltration membrane substrate according to claim 6, characterized in that, The temperature of the aqueous coagulation bath is any value between 10℃ and 30℃.
Citation Information
Patent Citations
Polyacrylonitrile porous hollow fiber membrane
CN121588647A
Preparation method of solvent-resistant ternary copolymerized COF membrane and application of solvent-resistant ternary copolymerized COF membrane in aromatic methanol separation
CN122352052A
